Anatomy of a Credit Crunch : From Capital to Labor Markets - Buera, Francisco J. (Elsevier, 2014)
Why are financial crises associated with a sustained rise in unemployment? We develop a tractable model with frictions in both credit and labor markets to study the aggregate and micro-level implications of a credit crunch—i.e., a sudden tightening of collateral constraints. When we simulate a credit crunch calibrated to match the observed decline in the ratio of debt to non-financial assets of the United States business sector following the 2007–2008 crisis, our model generates a sharp decline in output—explained by a drop in aggregate total factor productivity and investment—and a protracted increase in unemployment. We then explore the micro-level impact by tracking the employment dynamics for firms of different sizes and ages. The credit crunch causes a much larger reduction in the net employment growth rate of small, young establishments relative to that of large, old producers, consistent with the recent empirical findings in the literature.